Curcumin nanoparticles as a natural antioxidant and antimicrobial preservative against foodborne pathogens in processed chicken fingers - Morsy, Mohamed K.; Al-Dalain, Sati Y.; Haddad, Moawiya A.; Diab, Mohamed; Abd-Elaaty, Elsayed M.; Abdeen, Ahmed; Ibrahim, Samah F.; Shukry, Mustafa; Banatean-Dunea, Ioan; Fericean, Liana; Ghamry, Heba I.; El-Sayed, Amal; et al. (Frontiers in Sustainable Food Systems, 2023)
Introduction Curcumin has highly antimicrobial and antioxidant activities but has poor bioavailability and low solubility in water. The current study aimed to assess curcumin nanoparticles (Curcumin-NPs) antibacterial and antioxidant efficacy against some pathogens in chicken fingers at 4 °C/27 days. Methods Curcumin-NPs with particle sizes of 80 ± 2 nm were synthesized using a planetary ball-mill and chitosan-gelatin nanoparticle (CS-G-NPs) solution and then placed into chicken fingers at three concentrations, (2, 5, and 10 μg g−1). The physicochemical properties, antioxidant activity, and antibacterial capacity were evaluated. Results and discussion Curcumin-NPs showed high phenolic content (67.48 mg GAE g−1) and antioxidant activity (22.47 μg ml−1) at 10 μg g−1 compared to other concentrations and curcumin bulk. Curcumin-NPs showed noticeably greater antibacterial ability (in vitro) against S. aureus (18 mm), E. coli (15 mm), and B. cereus (13 mm). In challenge studies, Curcumin-NPs effectively inhibited the three inoculated pathogens 3–4 log CFU g−1; in vivo; in chicken fingers kept for up to 27 days, compared to the control. In curcumin-NPs chicken samples, the contents of thiobarbituric acid reactive substances (TBARS) and total volatile base nitrogen (TVB-N) compared to the control were substantially lower (27 days). TEM analysis provided an estimate of the antibacterial mechanism of Curcumin-NPs. The findings demonstrated that Curcumin-NPs at 10 μg g−1 were more successful in reducing microbial load in chicken fingers as well as improving quality parameters, enhancing shelf life, and reducing lipid oxidation in poultry meat products.